Engineering Process Of Deodorization To Improve Product Quality Of Red Palm Oil With Rich Of Carotene - Mursalin, Mursalin; Andarwulan, Nuri; Hariyadi, Purwiyatno (Department of Technology of Agricultural product (THP) Jambi University, 2017)
Abstract— Efforts to develop the production technology of high quality red palm-oil (RPO) in order to provide source of food ingredient that naturally rich of nutrients, become urgents regarding the need of such products drastically increased recently. Application of deodorization technology by temperature, time, and deodorizer pressure combinations (engineering of deodorization process) are studied and evaluated to obtain good quality of RPO. Crude palm oil (CPO) used in this research were supplied by PT. Salim Ivomas (Bimoli) Jakarta. The equipments used were degumming and neutralization unit, deodorization unit and other equipment units to analize the oil physico-chemical properties. The research consisted of 5 stages as the following: characterising CPO physico-chemical properties, conducting chemically degumming and deacidification, process enginering of deodorization, characterizing of physico-chemical properties and organoleptic of RPO resulted, and analyzing data for product resulted from process engineering applied. Deodorization with the range of temperature and process duration of 135–145 oC (408–418 K) and 1–4 hours have led to carotene retention decreasing (%) following the equation “Carotene Retention (%) = -764 x ln(absolute temperature) + 4693” and process duration with the equation “Carotene Retention (%) = -7.81 x ln(process duration) + 91.02”; and also resulted odor intensity with the equation “Odor Intensity = 0.08 x (squared absolute temperature) – 66.88 x (absolute temperature) + 13823” and duration process with the equation “Odor Intensity = 0.315 x (squared process duration) – 1.52 x (process duration) + 5.268”. Effective deodorization to produce RPO with the content of free fatty acid and peroxide value that met the requirements of Indonesian National Standard (SNI) quality of carotene content above 400 ppm and odor scale below 3.3, were the combination of temperature (T) of 141.34 oC, heat process duration (t) of 2.35 hours and vacuum pressure of (P) of 20 mmHg. The resulted RPO contained free fatty acid and peroxide value of 0.11% dan 0.12 meq/kg oil respectively, total carotene of 444.09 ppm and odor value of 3.21